2015
DOI: 10.4081/jlimnol.2015.1304
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ecological quality in peri-urban rivers in Mexico City: a proposal for identifying and validating reference sites using benthic macroinvertebrates as indicators

Abstract: Conservation and management of aquatic ecosystems that are significantly influenced by urban activities requires the classification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The orders Ephemeroptera, Plecoptera, and Trichoptera (EPT) are characteristic of oligotrophic waters and environments with good ecological quality (Merritt et al 2008). Their presence can help determine the state of conservation of the springs, and their disappearance can be attributed to an alteration in habitat and/or physical-chemical characteristics (Tierno de Figueroa and López 2015; Caro-Borrero et al 2016). According to Carmona-Jiménez and Caro-Borrero (2017) and Caro et al (2016), there are 37 families of benthic macroinvertebrates reported in the Magdalena River, of which 65% were found in this research.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The orders Ephemeroptera, Plecoptera, and Trichoptera (EPT) are characteristic of oligotrophic waters and environments with good ecological quality (Merritt et al 2008). Their presence can help determine the state of conservation of the springs, and their disappearance can be attributed to an alteration in habitat and/or physical-chemical characteristics (Tierno de Figueroa and López 2015; Caro-Borrero et al 2016). According to Carmona-Jiménez and Caro-Borrero (2017) and Caro et al (2016), there are 37 families of benthic macroinvertebrates reported in the Magdalena River, of which 65% were found in this research.…”
Section: Discussionmentioning
confidence: 66%
“…Likewise, larvae recorded in this study of the order Plecoptera (families Nemouridae and Perlodidae) are sensitive to habitat degradation and organic pollution (Merritt et al 2008;Gullan and Cranston 2010). These orders and families have already been recognized as good indicators of ecological quality both in the sub-basin (Caro-Borrero et al 2016) and at the regional level within the Basin of Mexico (Carmona-Jiménez and Caro-Borrero 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Spaces for new residential development within the city are fewer and the population continues to grow and demand more resources, increasing the production of waste, the emission of greenhouse gases, the number of fires, the illegal occupation of protected areas, and the depletion of available natural resources ( Santibáñez-Andrade et al 2015 ; SEMARNAT 2016 ; Heider et al 2018 ). Increased urbanization around Mexico City proper has also affected rivers and streams ( Caro-Borrero et al 2016 ). This considerable modification of the natural habitat exerts a constant pressure on the biological diversity of Mexico City.…”
Section: Introductionmentioning
confidence: 99%